In silico molecular docking study, synthesis and α-amylase inhibitory activity evaluation of phosphorylated derivatives of purine. (2nd November 2021) - Pavan Phani Kumar, M.; Anuradha, V.; Subramanyam, Ch.; Hari Babu, V. V.
Abstract: A series of phosphorylated derivatives of purine were synthesized in good yields (88–95%) by the reaction of 2‐chloro‐4‐[(9H‐purin‐9‐yl)methoxy]methyl‐1, 3, 2-λ 5 ‐dioxaphospholan‐2‐one with various heterocyclic amines. In silico molecular docking study was performed for all the designed compounds to assess their potential ability to inhibit the pancreatic α -amylase enzyme. The compounds (6a –j ) with good inhibition toward the target enzyme were prompted for the synthesis. Spectroscopic analyses of all the newly synthesized compounds were performed to confirm their structures. In vitro α -amylase inhibitory activity of the synthesized compounds was also carried out using acarbose as a standard drug. The compounds 2‐[(6‐chloro‐1, 3‐benzothiazol‐2‐yl)amino]‐4‐[(9H‐purin‐9‐yl)methoxy]methyl‐1, 3, 2λ 5 ‐dioxaphospholan‐2‐one (6j ) (IC50, 94.3 ± 0.5 μg/mL) and 1‐methyl‐6‐[(2‐oxo‐4‐[(9H‐purin‐9‐yl)methoxy]methyl‐1, 3, 2λ 5 ‐dioxaphospholan‐2‐yl)amino]‐1, 2, 3, 4‐tetrahydropyrimidine‐2, 4‐dione (6f ) (IC50, 99.0 ± 0.4 μg/mL) reported the highest inhibition among the synthesized compounds. All the remaining compounds exhibited good to moderate inhibition with IC50 values in the range of 102.9 ± 0.6 to 233.5 ± 0.6 μg/mL when compared with the standard drug, acarbose (IC50, 50.47 ± 0.28 μg/mL). Graphical Abstract: UF0001